2018
DOI: 10.1186/s13065-018-0430-5
|View full text |Cite
|
Sign up to set email alerts
|

BODIPY dyads and triads: synthesis, optical, electrochemical and transistor properties

Abstract: A series of D–A dyads and D–A–D triads molecular systems based on triphenylamine and 9-ethyl-carbarzole as donor (D) and BODIPY as acceptor (A) has been designed and synthesized. The optoelectronic properties including optical, electrochemical, and charge carrier mobility of these molecules have been investigated. We found that the D–A–D triads exhibited broader absorption, raising the HOMO energy levels and increase hole carrier mobilities. Analysis surface morphology revealed that BODIPY containing carbazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Our target BODIPY compounds, TPA-BODIPY-TPA (BODIPY-1) and CBZ-BODIPY-CBZ (BODIPY-2) (Figure 1), were synthesized following our previous report [49]. The chemical structures were confirmed using 1 H-NMR and 13 C-NMR, respectively (see Supplementary Materials, Figures S1-S6).…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Our target BODIPY compounds, TPA-BODIPY-TPA (BODIPY-1) and CBZ-BODIPY-CBZ (BODIPY-2) (Figure 1), were synthesized following our previous report [49]. The chemical structures were confirmed using 1 H-NMR and 13 C-NMR, respectively (see Supplementary Materials, Figures S1-S6).…”
Section: Synthesismentioning
confidence: 99%
“…Figure 7 presents the energy diagram of donor and acceptors. The HOMO and LUMO energy levels of BODIPY-1 and BODIPY-2 were estimated from our previous study [49]. The HOMO and LUMO offset (∆E) values between P3HT and BODIPY are about ∼0.1-0.2 eV, which are energetically feasible in term of driving the cascade charge transfer from P3HT to BODIPY and from BODIPY to PCBM [19,20].…”
Section: Proposed Operating Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Wanwong et al reported the application of beta -carbazole substituted BODIPY dyad and triad (Scheme 5; 15 and 16) as field effect transistors (FET). Though these derivatives provided moderate performance, modification of this structure may help to develop better dye with better performance (Wanwong et al, 2018).…”
Section: Beta-substituted Bodipysmentioning
confidence: 99%
“…[22][23][24]33 It is reported that the absorption and emission behavior of BODIPYs can be modified by the presence of an electron-rich carbazole moiety. 25,26 The linkage and the position at which carbazole is attached to the BODIPY scaffold play a major role. The structural diversity of the carbazole-BODIPY conjugates includes the BODIPY derivatives with carbazole rings at the alpha, beta, and meso-positions of the BODIPY skeleton.…”
Section: Introductionmentioning
confidence: 99%